Assessing Sense of School Belonging Across Cultural Contexts Using the PSSM: Measurement and Functional Invariance. (July 2016) - Abubakar, Amina; van de Vijver, Fons J. R.; Alonso-Arbiol, Itziar; Suryani, Angela O.; Pandia, Weny Savitry; Handani, Penny; Arasa, Josephine; Mazrui, Lubna; Murugumi, Margaret
Despite its popularity, the factorial structure of the Psychological Sense of School Membership (PSSM) Questionnaire remains controversial. The current study set out to clarify its structure across different cultural contexts. The study was carried out among 1, 928 adolescents aged 11 to 20 years in the Netherlands, Kenya, Indonesia, and Spain. Item-based measurement models with a single factor did not show a good fit. A bifactor method (defining a method factor for negatively worded items) did not show a good fit either. However, when items were combined per target to be rated (school, student, teacher, other people, and self), measurement invariance of a one-factorial model was found. Internal consistencies observed across the cultural groups studied were high. In addition, an evaluation of functional equivalence indicated that the relationship between PSSM and life satisfaction was invariant across countries. Implications for assessment and future directions are discussed.